"ORIF" for displaced intra-articular calcaneal fractures in children. Issue 2 (June 2015) - Al-Ashhab, Mohamed Ebrahim Ali
Highlights The characteristics of intra-articular calcaneal fractures in children are similar to those in adults. Operative treatment of these fractures, to restore calcaneal anatomical alignment yields good short-term results. Due to rarity of this fracture in children, we believe that a larger patient series with longer follow-up is needed to compare conservative versus operative treatment of pediatric calcaneal fractures.